Genomic and functional characterization of a Butyricicoccus porcorum strain isolated from human gut microbiota - Ni Zhao; Peiling Geng; Alejandro Gaher Perez; Anakha Chandramana Maya; Brijesh Yadav; Yuxuan Du; Yong Ge (mSystems)
ABSTRACT The gut is the most complex microbial ecosystem in the body that greatly influences human immune and metabolic health. However, the functional understanding of gut microbiome is hampered by our limited ability to obtain bacterial cultures for experimental validation, particularly low-abundant species that may carry specific functions but are often overlooked by population-based analyses. Here, we isolated and characterized a novel strain of Butyricicoccus porcorum (named Bp 531D) from human gut microbiota, representing the first butyrate-producing human isolate within a phylogenetic clade of Butyricicoccus complex. Comparative whole-genome analysis revealed a unique capability of Bp 531D for one-carbon metabolism and a high abundance of mobile genetic elements, including six prophages and plentiful transposons, reflecting its evolutionary flexibility. Oral administration of the bacterium profoundly altered gut microbiome composition in C57BL/6 mice, leading to controlled microbial oxidative signaling and calibrated carbohydrate metabolic function in the gut. RNA sequencing (RNA-seq) analysis demonstrated notable functional programming of colonic ECs, whereupon Bp 531D primarily restricted the biosynthesis of cholesterols and activated the pathway of antigen processing and presentation. Furthermore, the expression of MHC class II was correlatively heightened in colonic dendritic cells (DCs), and the frequencies of interleukin-10- (IL-10) and IL-22-producing T helper 17 (Th17) cells were significantly elevated in mice treated with Bp 531D compared to controls. Our findings uncover the crucial roles of B. porcorum in supporting intestinal homeostasis and provide a novel functional modulator to potentially optimize microbial strategies for improving intestinal health.IMPORTANCEReduced abundance of the Butyricicoccus genus has been associated with human intestinal disorders, including inflammatory bowel diseases. While supplementation of B. pullicaecorum mitigates intestinal inflammation, it is unclear whether other Butyricicoccus species critically contribute to intestinal microbial and immune homeostasis. We identified a novel Butyricicoccus species within human gut microbiota and characterized its detailed intestinal functions using the C57BL/6 mouse model. Our findings may further highlight the genetic and functional diversities of the gut microbiome.